REVIEW ARTIKEL: POTENSI FITOTERAPI DARI TANAMAN HERBAL DALAM PENANGANAN RHEUMATOID ARTHRITIS - Nurhayati, Ismaya; Maulani, Sintia Putri; Lathifah, Meira H.; Riasari, Hesti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by inflammation of the joints, resulting in progressive damage and a decreased quality of life for patients. Conventional therapies such as NSAIDs and DMARDs are indeed effective, but their long-term use carries the risk of serious side effects and high costs. Therefore, safer and more affordable alternative therapies are needed, one of which is through the use of medicinal plants. This study aims to examine the potential of herbal plants as an additional or alternative therapy for rheumatoid arthritis. The method employed is a literature study, involving the search and analysis of 31 scientific journals retrieved from academic databases, including Google Scholar, PubMed, ScienceDirect, and MDPI. The articles analyzed were selected based on certain criteria and contained information about the content of active compounds, pharmacological activity, and the mechanism of action of plants on the RA inflammation process. The results of the study showed that various herbal plants such as Zingiber officinale, Curcuma longa, Boswellia serrata, and Nigella sativa have significant anti-inflammatory and immunomodulatory activities. The active compounds in these plants work by inhibiting the inflammatory pathway and reducing the production of pro-inflammatory cytokines. In conclusion, medicinal plants have great potential to be used as additional therapy in the treatment of rheumatoid arthritis. However, further research is needed, especially clinical trials, to ensure the long-term safety and effectiveness of their use.